Entrapment of a metal foreign body in the heart during surgical procedure: A case report and literature review - Wang, Fei; Li, Ting; Yuan, Xinwei; Jiang, Hu (Frontiers in Surgery, 2022)
Abstract： Kerrsion Ronguer had been used to remove the thin bone in both orthopaedic surgery and neurosurgery, featured with a tip holding and cutting bone effectively while protecting the underlying instruments. The authors describe a case of a 40-year-old man proceeded the 2nd lumbar vertebrae osteotomy who presented to be ankylosing spondylitis with kyphosis and limited mobility for 10 years. During the surgery we found the rongeur tip was missing. The C-arm fluoroscopy showed the highly density body just in front of the vertebral body intraoperative. However, the CT scan testified the foreign body migrated to the right auricle of heart postoperative. This case is unique in that there was no exactly vessel injury detected intraoperative. There were few reports about the surgical instrument migrating to the heart. Our case showed the rare experience that function of multidisciplinary collaboration in the migration of foreign bodies in the cervical spinal canal.